2014
DOI: 10.1128/aac.01597-13
|View full text |Cite
|
Sign up to set email alerts
|

Biological Cost of Different Mechanisms of Colistin Resistance and Their Impact on Virulence in Acinetobacter baumannii

Abstract: e Two mechanisms of resistance to colistin have been described in Acinetobacter baumannii. One involves complete loss of lipopolysaccharide (LPS), resulting from mutations in lpxA, lpxC, or lpxD, and the second is associated with phosphoethanolamine addition to LPS, mediated through mutations in pmrAB. In order to assess the clinical impacts of both resistance mechanisms, A. baumannii ATCC 19606 and its isogenic derivatives, AL1851 ⌬lpxA, AL1852 ⌬lpxD, AL1842 ⌬lpxC, and ATCC 19606 pmrB, were analyzed for in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
171
2
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(197 citation statements)
references
References 45 publications
12
171
2
4
Order By: Relevance
“…Adams et al [40] Park et al [41] Lesho et al [42] Beceiro et al [44] Rolain et al [46] Kim et al [48] Arroyo et al [34] Snitkin et al [47] Choi et al [43] Choi et al [45] Colistin resistance and dependence in A. baumannii sule polysaccharide (CPS) and efflux pumps [54,55]. For CPS production, reduced production of CPS in colistin-resistant mutants was observed in Klebsiella pneumoniae, which is a contradictory finding [56].…”
Section: P233s A)mentioning
confidence: 94%
See 1 more Smart Citation
“…Adams et al [40] Park et al [41] Lesho et al [42] Beceiro et al [44] Rolain et al [46] Kim et al [48] Arroyo et al [34] Snitkin et al [47] Choi et al [43] Choi et al [45] Colistin resistance and dependence in A. baumannii sule polysaccharide (CPS) and efflux pumps [54,55]. For CPS production, reduced production of CPS in colistin-resistant mutants was observed in Klebsiella pneumoniae, which is a contradictory finding [56].…”
Section: P233s A)mentioning
confidence: 94%
“…Several studies have reported increased susceptibility to some antibiotics rather than polymyxins in LPS-deficient, colistin-resistant A. baumannii strains [51,52], which has been postulated to be due to an increase in the passive diffusion of antibiotics. Decreased virulence in LPS-deficient strains has also been observed, which is compared with no change in the virulence of colistin-resistant strains due to pmrAB mutations [44,53]. To date, colistin resistance through the loss of LPS has not been detected in bacteria other than Acinetobacter spp.…”
Section: Colistin Resistancementioning
confidence: 95%
“…No obstante, el CLSI no incorpora Tween-80 como coadyuvante para la determinación de CIM por microdilución, como sí lo hace en el caso del antibacteriano glucopéptido telavancina 6 . Por otro lado, se han planteado dos principales mecanismos de resistencia a colistín, uno de ellos por sustitución del lipopolisacárido (LPS) por fosfolípidos (mutación de genes lpx) 8 , y otro por adición de fosfoetanolamina al lípido A del LPS, ya sea por mutación del gen pmrB 8 o por adquisición de un plásmido portador de mcr-1 9 . En este sentido, sería necesario constatar en futuras investigaciones el tipo de mecanismo de resistencia presente en aislados clínicos chilenos.…”
Section: Discussionunclassified
“…Of interest, this experiment shows that in the absence of colistin, the mcr-1+ strain has a slight fitness defect [3]. Whether this is due to the mcr-1 gene itself or other genetic elements on pHNSHP45 is unknown, but it has been well documented that regulatory changes associated with colistin resistance often reduce the fitness of the organism containing those mutations in the absence of selection [6,7,16,17]. This suggests that removing the use of colistin may have the added benefit of selecting against the long-term survival of resistant isolates because of their reduced fitness relative to sensitive strains.…”
mentioning
confidence: 99%